Method for producing composite solid electrolyte
Patent Information
- Application Number
- JP2024545196
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-05-31
- Filing Date
- 2023-05-31
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-05-31
AI Technical Summary
【0014】 本発明による複合固体電解質の製造方法は、架橋結合性官能基を含む第1高分子及びセラミック化合物を含むセラミックイオン伝導体を形成することにより、リチウムイオンのイオン伝導を効果的に改善することができ、前記セラミックイオン伝導体を利用して複合固体電解質のイオン伝導度を向上させることができる。
Smart Images

Figure 2025504686000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0066945 filed on May 31, 2022 and Korean Patent Application No. 10-2023-0070136 filed on May 31, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.
[0002] The present invention relates to a method for producing a composite solid electrolyte. [Background technology]
[0003] Lithium-ion batteries that use liquid electrolytes have a structure in which the negative and positive electrodes are separated by a separator, so if the separator is damaged due to deformation or external impact, a short circuit can occur, which can lead to risks such as overheating and explosion. Therefore, the development of a solid electrolyte that can ensure safety in the field of lithium-ion secondary batteries is a very important issue.
[0004] Lithium secondary batteries using solid electrolytes have the advantages of increased safety, improved reliability due to the prevention of electrolyte leakage, and ease of manufacturing thin batteries. In addition, because lithium metal can be used for the negative electrode, the energy density can be improved, and this has led to expectations for applications in small secondary batteries as well as large-capacity secondary batteries for electric vehicles, and they are attracting attention as next-generation batteries.
[0005] Among solid electrolytes, polymer solid electrolytes may use either ion-conductive polymer materials or inorganic materials such as oxides and sulfides that have ion-conductive properties. Composite solid electrolytes that combine polymer and inorganic materials have also been proposed.
[0006] Such conventional composite solid electrolytes are manufactured by preparing a solution or slurry in which a polymer and an inorganic material are mixed and dispersed, and then subjecting the solution to solution casting on a substrate and a high-temperature drying process. However, the conventional composite solid electrolyte manufacturing technology has a limitation in that it is difficult to manufacture a composite solid electrolyte with improved ionic conductivity because the inorganic material is not uniformly dispersed in the polymer solution, resulting in non-uniform distribution of inorganic particles in the composite solid electrolyte.
[0007] In order to overcome these limitations of conventional composite solid electrolytes, there is a need to develop a method for manufacturing a composite solid electrolyte in which a polymer and an inorganic material are uniformly dispersed to improve the ionic conductivity of the composite solid electrolyte and which is capable of a continuous process. [Prior art documents] [Patent documents]
[0008] [Patent Document 1] Korean Patent Publication No. 10-2017-0045011 Summary of the Invention [Problem to be solved by the invention]
[0009] An object of the present invention is to provide a method for producing a composite solid electrolyte which has improved ionic conductivity and can be carried out in a continuous process.
[0010] Another object of the present invention is to provide an all-solid-state battery including the composite solid electrolyte produced by the above-mentioned production method. [Means for solving the problem]
[0011] In order to achieve the above objectives, The present invention includes a method for producing a ceramic composite layer by mixing a first polymer having a cross-linkable functional group with a ceramic compound in a first step; (2) a second step of sintering the first composite layer to produce a ceramic ionic conductor layer; and (3) a third step of coating the ceramic ion conductor layer with a composition including a second polymer and a lithium salt to produce a second composite layer; The present invention provides a method for producing a composite solid electrolyte, in which the first to third steps are carried out continuously.
[0012] The present invention also provides a composite solid electrolyte produced by the production method of the present invention, comprising a ceramic ion conductor layer containing a ceramic compound, a second polymer, and a lithium salt.
[0013] The present invention also provides an all-solid-state battery comprising the composite solid electrolyte produced by the production method of the present invention. Effect of the Invention
[0014] The method for preparing a composite solid electrolyte according to the present invention can effectively improve ionic conductivity of lithium ions by forming a ceramic ion conductor including a first polymer having a cross-linkable functional group and a ceramic compound, and can improve the ionic conductivity of the composite solid electrolyte by using the ceramic ion conductor.
[0015] Furthermore, the method for producing a composite solid electrolyte according to the present invention can produce the composite solid electrolyte in a continuous process, making mass production possible. [Brief description of the drawings]
[0016] [Figure 1] FIG. 1 is a flow chart of a method for producing a composite solid electrolyte of the present invention. [Diagram 2] FIG. 2 is an image taken of a first composite layer according to one embodiment of the present invention. [Diagram 3] FIG. 3 is an image of a ceramic ion conductor layer formed by sintering a first composite layer according to an embodiment of the present invention. [Figure 4]FIG. 4 is a scanning electron microscope (SEM) photograph of a ceramic compound (pristine LLZO) powder according to an embodiment of the present invention. [Diagram 5] FIG. 5 is a scanning electron microscope (SEM) photograph of a ceramic ion conductor layer according to an embodiment of the present invention. [Figure 6] FIG. 6 is an image taken of a first composite layer according to one embodiment of the present invention. [Figure 7] FIG. 7 is an image of a ceramic ion conductor layer according to one embodiment of the present invention. [Figure 8] FIG. 8 is an image of the ceramic ion conductor layer according to Comparative Example 1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] In the following, the present invention will be described in further detail to aid in understanding the invention.
[0018] The terms and words used in this specification and the claims should not be interpreted limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of the present invention, based on the principle that an inventor can appropriately define the concept of a term in order to best describe his / her invention.
[0019] In the conventional method of manufacturing a composite solid electrolyte, a solution or slurry in which a polymer and an inorganic material are mixed and dispersed is coated on a substrate film by a method such as solution casting, and then dried. However, this method has a problem in that the ionic conductivity of the solid electrolyte is not improved due to the non-uniform dispersion of the inorganic material in the polymer solution.
[0020] To improve this, the present invention provides a method for preparing a composite solid electrolyte by forming a first composite in the form of a hydrogel from a first polymer having a cross-linkable functional group and a ceramic compound, sintering the first composite, and then coating the first composite with a second polymer and a lithium salt.
[0021] In the method for producing a composite solid electrolyte of the present invention, a ceramic compound can be uniformly dispersed in the first composite to effectively form an ion conduction path for lithium ions, thereby obtaining a composite solid electrolyte having improved ion conductivity. The method for producing a composite solid electrolyte of the present invention can be produced in a continuous process, making it possible to mass-produce the composite solid electrolyte.
[0022] Method for producing composite solid electrolyte The present invention relates to a method for producing a composite solid electrolyte, and the method for producing a composite solid electrolyte of the present invention includes the steps of: (1) a first step of preparing a first composite layer by mixing a first polymer containing a cross-linkable functional group with a ceramic compound; (2) a second step of sintering the first composite layer to produce a ceramic ion conductor layer; (3) A third step of coating the ceramic ion conductor layer with a composition including a second polymer and a lithium salt to produce a second composite layer.
[0023] The first to third steps are carried out continuously.
[0024] The method for producing the composite solid electrolyte includes: producing a first composite layer in which ceramic compound particles are uniformly dispersed in the first polymer by hydrogelation of a first polymer; and sintering the first composite layer to efficiently produce a ceramic ion conductor layer, thereby improving the ion conductivity of lithium ions, and producing a composite solid electrolyte with improved ion conductivity.
[0025] Hereinafter, each step of the method for preparing the composite solid electrolyte according to the present invention will be described in detail.
[0026] The first step is a step of preparing a first composite layer by mixing a first polymer having a cross-linkable functional group with a ceramic compound.
[0027] The first composite layer is produced by hydrogelation of a first polymer, and has a form in which ceramic compound particles are uniformly dispersed in the first polymer in the form of a hydrogel. The first composite layer includes an amorphous polymer chain having a cross-linking structure between the first polymer and the ceramic compound and a cross-linking functional group, and the cross-linking structure includes (a) a cross-link between the cross-linking functional groups and (b) a cross-link between the cross-linking functional group and the ceramic compound.
[0028] The crosslinking bonds in (a) and (b) are physical crosslinking bonds or chemical crosslinking bonds.
[0029] The (a) cross-linking bond between the cross-linking functional groups includes a hydrogen bond between the cross-linking functional groups. For example, the hydrogen bond is an OH - The hydrogen bonds between the
[0030] The crosslinking between the (b) crosslinkable functional group and the ceramic compound includes a bond due to Lewis acid-base interaction, for example, the bond is a bond between an -OH group and Li. The crosslinking between the (b) crosslinkable functional group and the ceramic compound is a bond due to Lewis acid-base interaction, and is a type of crosslinking such as a metal-ligand bond.
[0031] In addition, the (b) crosslinking between the crosslinkable functional group and the ceramic compound prevents aggregation between particles of the ceramic compound and allows the particles of the ceramic compound to be uniformly dispersed in the hydrogel. Therefore, after forming a hydrogel of the first polymer to prepare a first composite layer, the first composite layer is sintered to prepare a ceramic ion conductor layer, which can improve the ion conductivity of the composite solid electrolyte.
[0032] The cross-linked structure improves the mobility of lithium ions within the electrolyte, making it possible to provide a composite solid electrolyte with improved ion conductivity.
[0033] In the present invention, the cross-linkable functional group contained in the first polymer has the property of being able to form a cross-linked structure by forming the bonds (a) and (b) described above.
[0034] For example, the cross-linkable functional group may include one or more selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
[0035] In addition, the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group is 80,000 g / mol to 130,000 g / mol, specifically, 80,000 g / mol or more, 83,000 g / mol or more, or 85,000 g / mol or more, and 90,000 g / mol or less, 110,000 g / mol or less, or 130,000 g / mol or less. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group is less than 80,000 g / mol, the bond due to the crosslinkable functional group may not be formed sufficiently to obtain a crosslinked structure. If the weight average molecular weight (Mw) of the polymer containing the crosslinkable functional group exceeds 130,000 g / mol, the entanglement of the polymer chain increases in the polymer solution used in the manufacturing process, and the solvent penetration rate into the inside of the polymer chain decreases. This may accelerate gelation of the polymer, reduce the solubility of the polymer, and inhibit smooth bonding via cross-linking functional groups, making it difficult to form a cross-linked structure.
[0036] In addition, the first polymer having a cross-linkable functional group may be selected from the group consisting of polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylamide), poly(acrylic acid) (PAA), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol. Preferably, the polymer having a cross-linkable functional group is PVA, which is advantageous in that phase separation between the PVA and a solvent is efficiently performed during freezing in the process of preparing a composite solid electrolyte, and the PVA is advantageous in that a cross-linked structure is formed by the bonds (a) and (b) induced from the cross-linkable functional group of the PVA phase-separated from the solvent.
[0037] The ceramic compound is an oxide-based or phosphate-based solid electrolyte. The oxide-based or phosphate-based solid electrolyte includes a garnet-type lithium-lanthanum-zirconium oxide (LLZO, Li 7 La 3 Zr 2 O 12 ), perovskite-type lithium-lanthanum-titanium oxide (LLTO, Li 3x La 2 / 3-x TiO 3 ), phosphate-based NASICON-type lithium-aluminum-titanium phosphate (LATP, Li 1+x Al x Ti 2-x (PO4 ) 3 ), lithium aluminum germanium phosphate (LAGP, Li 1.5 Al 0.5 Ge 1.5 (PO 4 ) 3 ) system, lithium-silicon-titanium phosphate system (LSTP, LiSiO 2 TiO 2 (PO 4 ) 3 ) and lithium-lanthanum-zirconium-titanium oxide (LLZTO) compounds. The oxide- or phosphate-based solid electrolytes have a very high grain boundary resistance, so a sintering process at 1000°C or higher is required. This causes problems such as lithium volatilization at high temperatures, phase transition, and impurity phase formation. However, oxide- or phosphate-based solid electrolytes generally have a maximum solubility of 10 -4 ~10 -3 It has an ionic conductivity value of 1.0 S / cm, is stable in the high voltage range, and is stable in air, so it has the advantages of being easy to synthesize and handle.
[0038] Therefore, by mixing the first polymer according to the present invention with a different material to prepare a composite solid electrolyte, the defects of each material can be compensated for.
[0039] The oxide-based or phosphate-based solid electrolyte has high high-temperature stability since it does not easily burn or ignite even under high-temperature conditions of 400° C. or more. Therefore, when the ceramic ion conductor includes the oxide-based or phosphate-based solid electrolyte, it can improve the mechanical strength as well as the high-temperature stability and ionic conductivity of the composite solid electrolyte for a lithium secondary battery.
[0040] Moreover, the first step is (1-1) preparing a first composite-forming composition comprising a first polymer having a cross-linkable functional group and a ceramic compound; (1-2) unwinding the base film using an unwinder and supplying it to a conveying path; (1-3) applying the composition for forming the first composite on the substrate film to form a coating film; (1-4) conveying the substrate film having the coating film formed thereon to a freezing section to freeze the coating film; (1-5) conveying the substrate film having the frozen coating film formed thereon to a thawing section to thaw the frozen coating film and form a physical cross-link between the first polymer and the ceramic compound to prepare a first composite layer; and (1-6) The method includes a step of winding and recovering the substrate film including the first composite layer using a rewinder.
[0041] The step (1-1) is a step of preparing a first composite-forming composition including a first polymer having a crosslinkable functional group and a ceramic compound.
[0042] The first composite-forming composition is prepared by adding a ceramic compound to a first polymer solution containing a cross-linkable functional group.
[0043] The solvent used in preparing the first polymer solution is a polar solvent, such as water, that is, the first polymer solution is an aqueous solution.
[0044] The concentration of the first polymer solution containing a crosslinkable functional group can be appropriately adjusted in consideration of the degree to which the coating process can proceed smoothly when the first complex-forming solution is applied to the base film. For example, the first polymer containing a crosslinkable functional group is contained in an amount of 5 to 20% by weight, specifically, 5% by weight or more, 7% by weight or more, or 9% by weight or more, and 13% by weight or less, 17% by weight or less, or 20% by weight or less, based on the total weight of the first polymer aqueous solution containing a crosslinkable functional group. If the first polymer containing a crosslinkable functional group is contained in an amount of less than 5% by weight, the concentration is too low and may run off when applied to the base film, and if it is contained in an amount of more than 20% by weight, it may be difficult to apply the first polymer in a uniform thin film form.
[0045] The ceramic compound is contained in an amount of 1 part by weight or more and less than 10 parts by weight per part by weight of the first polymer having the cross-linking functional group. More specifically, the weight ratio of the first polymer to the ceramic compound may be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or 1:9. If the ceramic compound is contained in an amount of less than 1 part by weight per part by weight of the first polymer, the ceramic compounds are not bonded smoothly after the sintering process in step (2) described below, making it difficult to form a ceramic ion conductor having a cross-linking structure, and the ceramic compound is easily broken or destroyed due to its weak mechanical properties, making it impossible to manufacture a composite solid electrolyte. In addition, if the ceramic compound is contained in an amount of more than 10 parts by weight per 1 part by weight of the first polymer, the ceramic compound is not uniformly dispersed in the first polymer, and the ceramic compound particles aggregate with each other, causing phase separation between the first polymer and the aggregated ceramic compound particles, making it difficult to form a ceramic ion conductor layer, resulting in a problem that a composite solid electrolyte having reduced ion conductivity is produced.
[0046] The step (1-2) is a step of unwinding the base film using an unwinder and supplying it to a transport path.
[0047] The unwinder winds up and supplies the base film wound in a roll shape to a predetermined transport path, and can unwind and supply the base film by its own drive, or can unwind and supply the base film by the drive force of a rewinder that winds up the base film including the first composite.
[0048] Thus, the first process of the present invention can be a roll-to-roll process.
[0049] The substrate film is not particularly limited as long as it can play a role as a support on which the first composite-forming composition is applied. For example, the substrate film is SS (stainless steel), polyethylene terephthalate film, polytetrafluoroethylene film, polyethylene film, polypropylene film, polybutene film, polybutadiene film, vinyl chloride copolymer film, polyurethane film, ethylene-vinyl acetate film, ethylene-propylene copolymer film, ethylene-ethyl acrylate copolymer film, ethylene-methyl acrylate copolymer film, or polyimide film.
[0050] The step (1-3) is a step of coating the first composite-forming composition on the substrate film to form a coating film.
[0051] The coating method in the present invention is not particularly limited as long as it can coat the composition for forming the first complex on the substrate film in the form of a film, for example, bar coating, roll coating, spin coating, slit coating, die coating, blade coating, comma coating, slot die coating, lip coating, spray coating, or solution casting.
[0052] In one embodiment of the present invention, a solution casting method can be used. More specifically, the composition for forming the first composite prepared in step (1-1) is placed in a mixer, and the mixer is placed above a substrate film, and the composition for forming the first composite is continuously cast onto the substrate film being fed to a transport path to form a coating film.
[0053] The step (1-4) is a step of conveying the substrate film having the coating film formed thereon to a freezing section to freeze the coating film, and the first composite layer can be produced in the step (1-4).
[0054] In the step (1-4), phase separation may occur between the first polymer and water contained in the first polymer aqueous solution containing the cross-linkable functional group. The phase separation can be induced because the strength of the hydrogen bonds between the water molecules is stronger than that between the cross-linkable functional group and the water molecules. The water molecules aggregated by the hydrogen bonds between the water molecules exist in an ice phase through a freezing process. As a result, the number of cross-linkable functional groups that form hydrogen bonds through interaction with the water molecules is significantly reduced.
[0055] Due to the phase separation, the inside of the coating film is divided into (i) a polymer-poor phase and (ii) a polymer-rich phase.
[0056] The (i) polymer-poor phase is a portion that contains water molecules that are aggregated by hydrogen bonds between water molecules, and exists in an ice phase, which can also be called a free water state.
[0057] The (ii) polymer-rich phase is a portion containing a polymer that has been phase-separated from water. The phase-separated polymer is a polymer containing cross-linking functional groups that has been freed from interactions with water molecules, and after phase separation, it is in a free state and does not form crystals through regular folding, but exists in an amorphous state with relatively free behavior, which is called an amorphous polymer chain.
[0058] In addition, some of the cross-linkable functional groups contained in the phase-separated polymer form localized crystallites, which act as cross-linkable junction points to form a cross-linked structure including the bonds (a) and (b).
[0059] The freezing of the coating film in step (1-4) can be performed by appropriately selecting conditions that can freeze the coating film. For example, the freezing temperature can be -30°C to -10°C, and specifically, the freezing temperature is -30°C or higher, -25°C or higher, or -23°C or higher, and -18°C or lower, -15°C or lower, or -10°C or lower. If the freezing temperature is lower than -30°C, cracks may occur in the coating film, and if it exceeds -10°C, phase separation between the polymer and water may not be sufficient, making it difficult to form an amorphous polymer chain region. Also, the freezing is performed in consideration of a time period that allows sufficient freezing within a range of 20 to 30 hours.
[0060] The freezing section is a section where a coating film is formed on a base film and the base film on which the coating film is formed is transported to a rewinder, and is configured with a plurality of freezing sections.
[0061] The step (1-5) is a step of conveying the substrate film having the frozen coating film formed thereon to a thawing section and thawing the frozen coating film to prepare a first composite layer.
[0062] In the step (1-5), the ice contained in the polymer-poor phase (i) melts and evaporates, thereby producing a first composite layer having an increased free volume.
[0063] The thawing can be performed by appropriately selecting conditions that allow the frozen coating film to be thawed to a degree that allows it to be applied to a polymer solid electrolyte. For example, the thawing temperature is 15° C. to 35° C., or room temperature (25° C.). If the thawing temperature is less than 15° C., the efficiency of drying water after thawing (ice melting) may decrease, and if it exceeds 35° C., the coating film may shrink and wrinkle or warp may occur.
[0064] As described above, through the steps (1-4) of freezing the coating film and (1-5) of thawing the frozen coating film, the defect freezing of (a) and (b) is induced to form a cross-linked structure and an amorphous polymer chain is formed.
[0065] Therefore, the steps (1-4) and (1-5) can be repeated, and the degree of formation of the cross-linked structure can be adjusted depending on the number of times the steps (1-4) and (1-5) are repeated. When the steps (1-4) and (1-5) are regarded as one cycle, the step (1-4) of freezing the coating film and the step (1-5) of thawing the frozen coating film can be performed for one or more cycles, two or more cycles, three or more cycles, or five or more cycles. The upper limit of the cycle is not particularly limited, and is 10 cycles or less, 13 cycles or less, or 15 cycles or less. As the number of cycles increases within the range, the more cross-linked structures are formed, and thus the modulus and strength of the polymer solid electrolyte are increased.
[0066] Once the thawing is complete in step (1-5), the coating film can be applied as a first composite layer.
[0067] The thawing section is located within a section in which the substrate film having the frozen coating film formed thereon is transported to a rewinder, and is composed of a plurality of units.
[0068] Furthermore, a chemical cross-linker may be added to the composition for forming the first composite in step (1-1), and a cross-linked structure between the first polymer and the ceramic compound is formed in step (1-4) by the chemical cross-linker.
[0069] In the first composite layer, a crosslinked structure and amorphous polymer chains are formed by physical crosslinking during freezing in step (1-4). If a chemical crosslinking agent is added in step (1-1) as described above, the crosslinked structure may also be formed by chemical crosslinking.
[0070] Specifically, the chemical cross-linking agent may form cross-links between the first polymer containing cross-linkable functional groups and the ceramic compound to form a cross-linked structure.
[0071] The chemical crosslinking agent can form bonds between the first polymer containing the crosslinkable functional groups or between the first polymer containing the crosslinkable functional groups and the ceramic compound.
[0072] The chemical crosslinking agent may include at least one selected from the group consisting of boric acid, glutaraldehyde, inorganic salts, and metal salts, but is not limited to these examples, and may be any chemical crosslinking agent that forms a hydrogel of the first polymer.
[0073] The step (1-6) is a step of winding and recovering the substrate film including the first composite layer using a rewinder.
[0074] The rewinder can wind up the base film including the first composite layer into a roll and recover it, and can wind up the base film including the first composite layer by its own drive.
[0075] In the method for producing the composite solid electrolyte of the present invention, the first step is a roll-to-roll process, which allows for continuous production.
[0076] The second step may be carried out continuously after the step (1-6). The second step includes: (2-1) unwinding the base film including the first composite layer using an unwinder, peeling the first composite layer from the base film, and slitting the first composite layer; and (2-2) Sintering the substrate film including the slit first composite layer to produce a ceramic ion conductor layer.
[0077] The step (2-1) is a step of unwinding the base film including the first composite layer using an unwinder, peeling the first composite layer from the base film, and slitting the first composite layer.
[0078] The unwinder winds up and supplies the base film including the first composite layer wound in a roll along a predetermined transport path, and can unwind and supply the base film including the first composite layer by its own drive.
[0079] Thereafter, the first composite layer is peeled off from the base film, and then slitting is performed to a desired area.
[0080] The step (2-2) is a step of sintering the slit first composite layer to manufacture a ceramic ion conductor layer.
[0081] As used herein, sintering refers to the process of subjecting the first composite layer to sufficient temperature and pressure to reduce it to a harder mass of particles.
[0082] The ceramic ion conductor is manufactured by sintering the first composite layer and pyrolyzing it, and sintering the remaining ceramic compound particles.
[0083] Through the sintering process, the first polymer acts as a support to allow the particles of the ceramic compound to be connected to each other, and the particles of the ceramic compound are connected to each other to form a ceramic ion conductor layer having a cross-linked structure.
[0084] The ceramic ion conductor layer comprises a cross-linked structure that includes a ceramic compound.
[0085] The ceramic ion conductor layer serves to form an ion conduction path for lithium ions.
[0086] The sintering can be performed under suitable conditions such that the first composite layer is pyrolyzed and the ceramic compound grain structures are linked to each other to form a ceramic ion conductor layer having a cross-linked structure. For example, the sintering can be performed at a temperature of 800°C to 1300°C, and more specifically, the sintering temperature is 850°C or more, 900°C or more, or 950°C or more, and 1300°C or less, 1250°C or less, or 1200°C or less.
[0087] The third step may be carried out consecutively after the step (2-2). The third step includes: (3-1) preparing a composition comprising a second polymer and a lithium salt; (3-2) coating the ceramic ion conductor layer with the composition; and (3-3) drying the ceramic ion conductor layer coated with the composition to form a second composite layer.
[0088] The second composite layer includes the ceramic ion conductor layer, so that a composite solid electrolyte having improved ion conductivity can be produced.
[0089] The step (3-1) is a step of preparing a composition including a second polymer and a lithium salt.
[0090] The second polymer has excellent solubility for lithium salts, and the polymer solution easily permeates the ceramic ion conductor, facilitating the final production of a composite solid electrolyte. Specific examples of the second polymer may include at least one selected from the group consisting of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate (PMMA), PSTFSI, polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylic amide), poly(acrylic acid), starch-carboxymethylcellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
[0091] In the present invention, the lithium salt is contained in a dissociated state within the structure formed by the ceramic ion conductor layer, thereby improving the ionic conductivity of the composite solid electrolyte. Also, the lithium salt is mainly dissociated within the second polymer, thereby compensating for the loss of lithium ions generated from the ceramic compound particles during the high-temperature sintering process in the second step.
[0092] The lithium salt is LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 Cl 10, LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 , (CF 3 SO 2 ) 2 NLi and (FSO 2 ) 2 NLi.
[0093] The composition is prepared by adding a lithium salt to a solution containing a second polymer.
[0094] The solvent used in preparing the second polymer solution is a polar solvent, such as water, that is, the second polymer solution is an aqueous polymer solution.
[0095] The concentration of the solution containing the second polymer can be appropriately adjusted in consideration of the smooth progress of the coating process for coating the ceramic ion conductor layer. For example, the second polymer is contained in an amount of 5 to 20 wt %, specifically, 5 wt % or more, 7 wt % or more, or 9 wt % or more, and 13 wt % or less, 17 wt % or less, or 20 wt % or less, based on the total weight of the second polymer solution. If the second polymer is contained in an amount less than 5 wt %, the concentration is too dilute and the surface of the ceramic ion conductor layer cannot be coated, whereas if the second polymer is contained in an amount more than 20 wt %, the concentration is too high and it is difficult to uniformly coat the surface of the ceramic ion conductor layer.
[0096] The molar ratio ([Li] / [G]) of the second polymer to the lithium ([Li]) of the lithium salt is 0.1 to 0.5, specifically, 0.1 or more, 0.2 or more, or 0.3 or more, and 0.4 or less, or 0.5 or less. If the molar ratio ([Li] / [G]) is less than 0.1, the content of the lithium salt may decrease, and the ionic conductivity of the composite solid electrolyte may decrease. If the molar ratio ([Li] / [G]) is more than 0.5, the ionic conductivity may decrease due to the aggregation of lithium ions. Therefore, the composite solid electrolyte according to the present invention requires a composition of the second polymer and an appropriate amount of lithium salt in the second composite layer.
[0097] The step (3-2) is a step of coating the ceramic ion conductor layer with the composition.
[0098] The coating method is not particularly limited as long as it is a method commonly used in the art, and dipping, spraying, doctor blade, spin coating, etc. can be used, and dipping is preferably used.
[0099] The step (3-3) is a step of drying the ceramic ion conductor layer coated with the composition to form a second composite body.
[0100] The drying can be carried out in an oven. The drying temperature is not particularly limited as long as it is a temperature at which the composition can be dried, but is preferably a temperature of 80 to 100°C.
[0101] Moreover, the coating step (3-2) and the drying step (3-3) can be repeated multiple times.
[0102] The ceramic ion conductor layer coated with the second composite layer is the composite solid electrolyte to be prepared in the present invention, and the composite solid electrolyte has improved ion conductivity, specifically, 10 -5Although the composite solid electrolyte is a solid electrolyte, it exhibits ion conductivity at a level equal to or higher than that of conventional liquid electrolytes, and can improve the performance of all-solid-state batteries.
[0103] The method for producing the composite solid electrolyte of the present invention is a continuous process in which the first to third steps are carried out continuously, and thus mass production is possible.
[0104] Composite solid electrolyte The present invention also relates to a composite solid electrolyte comprising a conductor layer containing a ceramic compound, a second polymer, and a lithium salt, the composite solid electrolyte being produced by the above-mentioned production method of the present invention.
[0105] The ceramic ion conductor layer, the second polymer, and the lithium salt are the same as those described above.
[0106] The ceramic ion conductor layer is obtained by sintering the first composite layer described above, and therefore includes a cross-linked structure between the first polymer having a cross-linkable functional group and the ceramic compound.
[0107] Conventional composite solid electrolytes are manufactured by coating a solution or slurry in which a polymer and an inorganic material are mixed and dispersed on a substrate by a method such as solution casting, and then drying the coated solution or slurry. However, this method has a problem in that the ionic conductivity of the solid electrolyte is not improved due to non-uniform dispersion and precipitation of the inorganic material in the polymer solution.
[0108] In order to improve this, the present invention provides a composite solid electrolyte including a ceramic ion conductor layer having a cross-linked structure forming an ion conduction path for lithium ions, a second polymer, and a lithium salt. The ceramic ion conductor has ceramic compound particles uniformly dispersed therein, and can play a role in improving the ion conductivity of the composite solid electrolyte.
[0109] The composite solid electrolyte is in the form of a free standing film. The free standing film means a film that can maintain a film shape by itself without a separate support at room temperature and pressure.
[0110] The free-standing film exhibits elasticity and minimizes brittleness, and has the properties of a support that stably contains lithium ions, making it an appropriate form for a composite solid electrolyte.
[0111] In the present invention, the ionic conductivity of the composite solid electrolyte is 10 -5 S / cm or more.
[0112] Although the composite solid electrolyte is a solid electrolyte, it exhibits ionic conductivity at a level equal to or higher than that of conventional liquid electrolytes, and can improve the performance of all-solid-state batteries.
[0113] All solid state battery The present invention also relates to an all-solid-state battery including the composite solid electrolyte, the all-solid-state battery including a negative electrode, a positive electrode, and a composite solid electrolyte interposed between the negative electrode and the positive electrode, the composite solid electrolyte being produced by the production method and having the characteristics described above.
[0114] Specifically, the composite solid electrolyte contains a ceramic ion conductor and improves the ion conduction of lithium ions, making it suitable as an electrolyte for an all-solid-state battery.
[0115] In the present invention, the positive electrode included in the all-solid-state battery may include a positive electrode active material layer, and the positive electrode active material layer may be formed on one surface of a positive electrode current collector.
[0116] The positive electrode active material layer includes a positive electrode active material, a binder, and a conductive material.
[0117] The positive electrode active material is not particularly limited as long as it is a material capable of reversibly absorbing and releasing lithium ions. For example, lithium cobalt oxide (LiCoO 2 ), lithium nickel oxide (LiNiO 2 ), Li[Ni x Co y Mn z M v ]O 2 (wherein M is any one or more elements selected from the group consisting of Al, Ga, and In, and 0.3≦x<1.0, 0≦y, z≦0.5, 0≦v≦0.1, and x+y+z+v=1), Li (Li a M b-a-b’ M' b’ )O 2-c A c (wherein, 0≦a≦0.2, 0.6≦b≦1, 0≦b'≦0.2, 0≦c≦0.2, M includes Mn and at least one selected from the group consisting of Ni, Co, Fe, Cr, V, Cu, Zn, and Ti, M' is at least one selected from the group consisting of Al, Mg, and B, and A is at least one selected from the group consisting of P, F, S, and N), or a compound substituted with one or more transition metals, a compound of the formula Li 1+y Mn 2-y O 4 (where y is 0 - 0.33), LiMnO 3 , LiMn 2 O 3 , LiMnO 2 Lithium manganese oxide, lithium copper oxide (Li 2 CuO 2 ), LiV 3 O 8 , Life 3 O 4 , V 2 O 5 , Cu 2 V 2 O 7 Vanadium oxides such as LiNi 1-y MyO 2(where M=Co, Mn, Al, Cu, Fe, Fe, Mg, B or Ga, and y=0.01 - 0.3), 2-y M y O 2 (where M=Co, Ni, Fe, Cr, Zn or Ta and y=0.01 - 0.1) or Li 2 Mn 3 MO 8 Lithium manganese oxides represented by the formula LiMn (where M=Fe, Co, Co, Ni, Cu or Zn) are used. 2 O 4 , disulfide compounds, Fe 2 (MoO 4 ) 3 These include, but are not limited to:
[0118] The positive electrode active material is contained in an amount of 40 to 80 wt % based on the total weight of the positive electrode active material layer. Specifically, the content of the positive electrode active material is 40 wt % or more or 50 wt % or more and 70 wt % or less or 80 wt % or less. If the content of the positive electrode active material is less than 40 wt %, the connectivity between the wet positive electrode active material layer and the dry positive electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0119] The binder is a component that assists in binding the positive electrode active material to the conductive material and the like and binding to the current collector, and is preferably a rubber such as styrene-butadiene rubber, acrylated styrene-butadiene rubber, acrylonitrile copolymer, acrylonitrile-butadiene rubber, nitrile butadiene rubber, acrylonitrile-styrene-butadiene copolymer, acrylic rubber, butyl rubber, fluororubber, polytetrafluoroethylene, polyethylene, polypropylene, ethylene / propylene copolymer, polybutadiene, polyethylene oxide, chlorosulfonated polyethylene, polyvinylpyrrolidone, polyvinylpyridine, polyvinyl alcohol, polyvinyl acetate, polyvinyl chloride, polyphosphazene, polyacrylonitrile, etc. The binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polystyrene, latex, acrylic resin, phenolic resin, epoxy resin, carboxymethylcellulose, hydroxypropylcellulose, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethylcellulose, cyanoethylsucrose, polyester, polyamide, polyether, polyimide, polycarboxylate, polycarboxylic acid, polyacrylic acid, polyacrylate, lithium polyacrylate, polymethacrylic acid, polymethacrylate, polyacrylamide, polyurethane, polyvinylidene fluoride, and poly(vinylidene fluoride)-hexafluoropropene. Preferably, the binder may include at least one selected from the group consisting of styrene-butadiene rubber, polytetrafluoroethylene, carboxymethylcellulose, polyacrylic acid, lithium polyacrylate, and polyvinylidene fluoride.
[0120] The binder is contained in an amount of 1 wt% to 30 wt% based on the total weight of the positive electrode active material layer, and specifically, the binder content is 1 wt% or more or 3 wt% or more and 15 wt% or less or 30 wt% or less. If the binder content is less than 1 wt%, the adhesive strength between the positive electrode active material and the positive electrode current collector may decrease, and if it exceeds 30 wt%, the adhesive strength is improved, but the content of the positive electrode active material decreases accordingly, and the battery capacity may decrease.
[0121] The conductive material is not particularly limited as long as it prevents side reactions in the internal environment of the all-solid-state battery and has excellent electrical conductivity without causing chemical changes in the battery. Representative examples include graphite or conductive carbon. For example, graphite such as natural graphite and artificial graphite, carbon black, acetylene black, ketjen black, denka black, thermal black, channel black, furnace black, lamp black, summer black, and other carbon blacks, carbon-based substances having a graphene or graphite crystal structure, conductive fibers such as carbon fibers and metal fibers, metal powders such as carbon fluoride, aluminum powder, and nickel powder, conductive whiskey such as zinc oxide and potassium titanate, conductive oxides such as titanium oxide, and conductive polymers such as polyphenylene derivatives can be used alone or in a mixture of two or more kinds, but are not limited thereto.
[0122] The conductive material is usually included in an amount of 0.5 wt % to 30 wt % based on the total weight of the positive electrode active material layer, and specifically, the content of the conductive material is 0.5 wt % or more or 1 wt % or more and 20 wt % or less or 30 wt % or less. If the content of the conductive material is too small, such as less than 0.5 wt %, it is difficult to expect an improvement in electrical conductivity, and the electrochemical properties of the battery may be deteriorated, and if the content is too large, such as more than 30 wt %, the amount of the positive electrode active material may be relatively small, and the capacity and energy density may be reduced. The method of incorporating the conductive material into the positive electrode is not significantly limited, and a conventional method known in the art, such as coating on the positive electrode active material, may be used.
[0123] The positive electrode current collector supports the positive electrode active material layer and transfers electrons between an external conductor and the positive electrode active material layer.
[0124] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the all-solid-state battery and has high electronic conductivity. For example, the positive electrode current collector can be made of copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, or the like, or an aluminum-cadmium alloy.
[0125] The positive electrode current collector may have a fine uneven structure or a three-dimensional porous structure on the surface thereof in order to strengthen the bonding force with the positive electrode active material layer, and thus the positive electrode current collector may have various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.
[0126] The positive electrode may be prepared according to a conventional method, specifically, by mixing a positive electrode active material, a conductive material, and a binder in an organic solvent to prepare a composition for forming a positive electrode active material layer, applying the composition onto a positive electrode current collector, drying the composition, and optionally compressing the composition into a current collector to improve the electrode density. At this time, it is preferable to use an organic solvent that can uniformly disperse the positive electrode active material, the binder, and the conductive material and that can be easily evaporated. Specific examples of the organic solvent include acetonitrile, methanol, ethanol, tetrahydrofuran, water, and isopropyl alcohol.
[0127] In the present invention, the negative electrode included in the all-solid-state battery includes a negative electrode active material layer, and the negative electrode active material layer is formed on one surface of a negative electrode current collector.
[0128] The negative electrode active material is a lithium ion (Li + The intercalation or deintercalation of lithium ions is not particularly limited, and may be carried out by any suitable method.
[0129] The lithium ion (Li +The material capable of reversibly inserting or de-inserting lithium ions (Li) is, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium (Li) to reversibly form a lithium-containing compound is, for example, tin oxide, titanate, or silicon. The lithium alloy is, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0130] Preferably, the negative electrode active material is lithium metal, specifically in the form of a lithium metal thin film or lithium metal powder.
[0131] The negative electrode active material may be contained in an amount of 40 to 80 wt % based on the total weight of the negative electrode active material layer. Specifically, the content of the negative electrode active material may be 40 wt % or more or 50 wt % or more and 70 wt % or less or 80 wt % or less. If the content of the negative electrode active material is less than 40 wt %, the connectivity between the wet negative electrode active material layer and the dry negative electrode active material layer may be insufficient, and if it exceeds 80 wt %, the mass transfer resistance may be large.
[0132] The binder is as described above in the positive electrode active material layer.
[0133] The conductive material is as described above in the positive electrode active material layer.
[0134] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and examples of the negative electrode current collector that can be used include copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, aluminum-cadmium alloy, etc. Similarly to the positive electrode current collector, the negative electrode current collector can be in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc., with fine irregularities formed on the surface.
[0135] The method for manufacturing the anode is not particularly limited, and the anode may be manufactured by forming an anode active material layer on the anode current collector using a method for forming a layer or film commonly used in the art. For example, methods such as compression bonding, coating, deposition, etc. may be used. In addition, the anode of the present invention may include a case where a lithium thin film is formed on the metal plate by initial charging after assembling a battery without a lithium thin film on the anode current collector.
[0136] The present invention also provides a battery module including the all-solid-state battery as a unit cell, a battery pack including the battery module, and a device including the battery pack as a power source.
[0137] In this case, specific examples of the device include, but are not limited to, power tools powered by an electric motor, electric vehicles including electric vehicles (EV), hybrid electric vehicles (HEV), plug-in hybrid electric vehicles (PHEV), etc., electric bicycles (E-bikes), electric two-wheeled vehicles including electric scooters (E-scooters), electric golf carts, and power storage systems.
[0138] Below, preferred examples are shown to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the category and technical spirit of the present invention. Naturally, these changes and modifications also fall within the scope of the appended claims.
[0139] In the examples and comparative examples described later, a ceramic ion conductor containing the first polymer and ceramic compound shown in Table 1 below was produced, and a composite solid electrolyte containing this was produced.
[0140] [Table 1]
[0141] Working Example Example 1 Preparation of composite solid electrolyte (1) Preparation of the first composite layer PVA (Mw: 89,000 g / mol, degree of hydrolysis: > 99%) was mixed with DI water to prepare a 10 wt% PVA aqueous solution. A solution was prepared by adding LLZO powder, a ceramic compound, to the PVA aqueous solution. The weight ratio of PVA to LLZO was 1:2.
[0142] The solution was poured into a mixer and then coated by solution casting onto a substrate film (SS foil) fed to a conveying path by an unwinder, which was then conveyed to a freezing section where it was frozen at -20°C for 24 hours, and then conveyed to a thawing section where it was thawed at 25°C to induce physical cross-linking of the PVA, thereby producing a first composite layer on the substrate film. The substrate film containing the produced first composite layer was wound and collected using a rewinder. The substrate film was then peeled off to obtain a hydrogel-like first composite layer.
[0143] (2) Fabrication of the ceramic ion conductor layer The first composite layer was peeled off from the substrate film including the first composite layer, which was fed to a transport path by an unwinder, and the peeled first composite layer was slit into a desired size. The slit first composite layer was heated from room temperature to 800° C. at a rate of 1° C. / min and sintered at 800° C. for 2 hours to thermally decompose the PVA hydrogel contained in the first composite layer and sinter the remaining LLZO particles to produce a ceramic ion conductor layer.
[0144] (3) Manufacturing of composite solid electrolyte A solution containing PEO and LiTFSI was prepared (wherein the molar ratio ([Li] / [O]) of "O" contained in PEO and "Li" contained in the lithium salt was 0.4). The ceramic ion conductor layer was immersed in the prepared solution for 5 minutes and then dried in a vacuum drying oven at a temperature of 100°C for 12 hours to prepare a composite solid electrolyte.
[0145] Example 2 A composite solid electrolyte was prepared in the same manner as in Example 1, except that LSTP was used instead of the ceramic compound LLZO.
[0146] Example 3 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 1:10.
[0147] Example 4 A composite solid electrolyte was prepared in the same manner as in Example 1, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 10:1.
[0148] Example 5 A composite solid electrolyte was prepared in the same manner as in Example 1, except that instead of the freezing and thawing process, 0.1 mL of boric acid (1 wt% aqueous solution) as a chemical cross-linker was added to 20 mL of the solution containing the polymer (PVA) and the ceramic compound, and the mixture was stirred at 200 rpm for 1 hour using a magnetic stirrer to prepare a hydrogel-like first composite layer by chemical cross-linking.
[0149] Example 6 A composite solid electrolyte was prepared in the same manner as in Example 5, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 1:10.
[0150] Example 7 A composite solid electrolyte was prepared in the same manner as in Example 5, except that the weight ratio of the polymer (PVA) and the ceramic compound (LLZO) was 10:1.
[0151] Comparative Example 1 A composite solid electrolyte was prepared in the same manner as in Example 1, except that a solution containing a polymer (PVA) and a ceramic compound (LLZO) was prepared, the solution was applied onto a glass slide as a substrate, and then the solution was dried at 80° C. for 12 hours instead of the freezing and thawing process.
[0152] Comparative Example 2 A composite solid electrolyte was prepared in the same manner as in Example 1, except that PEO (Mw: 4,000,000,000 g / mol), a polymer having no cross-linking functional group, was used instead of the polymer (PVA).
[0153] Comparative Example 3 A composite solid electrolyte was prepared in the same manner as in Example 1, except that a 35% aqueous solution of poly(acrylic acid) (Mw: 100,000 g / mol) was used instead of the polymer (PVA).
[0154] Experimental Example 1 In order to measure the ionic conductivity of the film-shaped composite solid electrolytes prepared in the examples and comparative examples, 2 The composite solid electrolyte was punched out into a circular shape of a desired size, and the punched composite solid electrolyte was placed between two pieces of stainless steel (SS) to fabricate a coin cell.
[0155] The resistance was measured using an electrochemical impedance spectrometer (EIS, VM3, Bio Logic Science Instrument) at 25° C. under conditions of an amplitude of 10 mV and a scan range of 500 KHz to 20 MHz, and the ionic conductivity of the composite solid electrolyte was calculated using Equation 1 below.
[0156]
number
[0157] In the above formula 1, σi is the ionic conductivity (S / cm) of the composite solid electrolyte, R is the resistance (Ω) of the composite solid electrolyte measured by the electrochemical impedance spectrometer, L is the thickness (μm) of the composite solid electrolyte, and A is the area (cm 2 )
[0158] The ionic conductivity of the composite solid electrolyte calculated using Equation 1, the presence or absence of hydrogel formation, the possibility of forming a freestanding film, and the results of observing the appearance of the composite solid electrolyte are shown in Table 2. At this time, the presence or absence of the hydrogel formation (formed: ◯, not formed: X), the possibility of forming a freestanding film (formed: ◯, not formed: X), and the appearance of the composite solid electrolyte were observed with the naked eye.
[0159] [Table 2]
[0160] As shown in Table 2, it was confirmed that a first composite layer was formed by subjecting a solution in which the first polymer having a cross-linkable functional group and the ceramic compound were mixed in an appropriate weight ratio to a freezing and thawing process, and the first composite layer was sintered to form a ceramic ion conductor layer, thereby producing a composite solid electrolyte (Examples 1, 2 and 5 (FIGS. 2 to 7)).
[0161] In Comparative Example 1, an electrolyte was prepared using a high-temperature drying process at 80° C., and a film having no cross-linked structure and weak mechanical properties was formed, and no ceramic ion conductor was formed after sintering.
[0162] Comparative Examples 2 and 3 were produced using a polymer not containing a cross-linking functional group, and a hydrogel-like first composite layer was not formed.
[0163] Although the present invention has been described above with reference to limited examples and drawings, the present invention is not limited thereto, and it goes without saying that various modifications and variations can be made by a person having ordinary knowledge in the technical field to which the present invention pertains within the technical spirit of the present invention and the equivalent scope of the claims described below.
Claims
1. (1) a first step of preparing a first composite layer by mixing a first polymer containing a cross-linkable functional group and a ceramic compound; (2) a second step of sintering the first composite layer to produce a ceramic ionic conductor layer; and (3) a third step of coating the ceramic ion conductor layer with a composition including a second polymer and a lithium salt to produce a second composite layer; The method for producing a composite solid electrolyte, wherein the first step, the second step, and the third step are carried out continuously.
2. The cross-linkable functional group includes at least one selected from the group consisting of a hydroxyl group, a carboxyl group, and an amide group.
3. The first polymer having a crosslinkable functional group includes polyvinyl alcohol (PVA), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylamide), starch-carboxymethylcellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
2. The method for producing a composite solid electrolyte according to claim 1, further comprising the step of:
4. 2. The method for producing a composite solid electrolyte according to claim 1, wherein the ceramic compound comprises at least one selected from the group consisting of lithium-lanthanum-zirconium oxide (LLZO), lithium-silicon-titanium phosphate (LSTP), lithium-lanthanum-titanium oxide (LLTO), lithium-aluminum-titanium phosphate (LATP), lithium-aluminum-germanium phosphate (LAGP) and lithium-lanthanum-zirconium-titanium oxide (LLZTO) compounds.
5. The method for producing a composite solid electrolyte according to claim 1 , wherein the ceramic compound is contained in an amount of 1 part by weight or more and less than 10 parts by weight per 1 part by weight of the first polymer.
6. The first step comprises: (1-1) preparing a first composite-forming composition comprising a first polymer having a cross-linkable functional group and a ceramic compound; (1-2) unwinding the base film using an unwinder and supplying it to a conveying path; (1-3) applying the composition for forming the first composite on the substrate film to form a coating film; (1-4) conveying the substrate film having the coating film formed thereon to a freezing section and freezing the coating film; (1-5) conveying the substrate film having the frozen coating film formed thereon to a thawing section to thaw the frozen coating film to prepare a first composite layer; and (1-6) A method for producing the composite solid electrolyte according to any one of claims 1 to 5, comprising a step of winding and recovering the substrate film including the first composite layer using a rewinder.
7. the first composite layer includes a cross-linked structure between the first polymer and a ceramic compound, and an amorphous polymer chain including a cross-linkable functional group; The cross-linked structure between the first polymer and the ceramic compound, and the amorphous polymer chains including the cross-linkable functional groups are formed in the step (1-4), The cross-linked structure is the (a) cross-linking bond between the cross-linkable functional groups includes a hydrogen bond, 7. The method for producing a composite solid electrolyte according to claim 6, wherein the (b) crosslinking between the crosslinkable functional group and the ceramic compound includes bonding through Lewis acid-base interaction.
8. 7. The method for producing a composite solid electrolyte according to claim 6, wherein a chemical cross-linker is added to the composition for forming the first composite in step (1-1), and a cross-linked structure between the first polymer and the ceramic compound and an amorphous polymer chain including the cross-linkable functional group are formed in step (1-4).
9. The method for producing a composite solid electrolyte according to claim 6, wherein the freezing is carried out at a temperature of -30°C to -10°C.
10. The method for producing a composite solid electrolyte according to claim 6, wherein the thawing is performed at 15°C to 35°C.
11. The method for producing a composite solid electrolyte according to claim 6, wherein the freezing in step (1-4) and the thawing in step (1-5) are repeated.
12. After step (1-6), the second step is: (2-1) unwinding the base film including the first composite layer using an unwinder, peeling the first composite layer from the base film, and slitting the first composite layer; and (2-2) The method for producing a composite solid electrolyte according to claim 6, further comprising the step of sintering the slit first composite layer to produce a ceramic ion conductor layer.
13. The method for producing a composite solid electrolyte according to claim 12, wherein the sintering is performed at 800°C to 1300°C.
14. After the step (2-2), the third step is: (3-1) preparing a composition comprising a second polymer and a lithium salt; (3-2) coating the ceramic ion conductor layer with the composition; and (3-3) The method for producing the composite solid electrolyte according to claim 6, further comprising the step of drying the coating layer to form a second composite layer.
15. The second polymer may be selected from the group consisting of polyvinyl alcohol (PVA), polyethylene oxide (PEO), polyacrylate, poly(methyl methacrylate (PMMA), PSTFSI, polyurethane, nylon, poly(dimethylsiloxane), gelatin, methylcellulose, agar, dextrin, poly(vinyl pyrrolidone), poly(acrylamide), and poly(acrylic acid).
2. The method for producing the composite solid electrolyte according to claim 1, wherein the composite solid electrolyte comprises at least one selected from the group consisting of poly(N-isopropylacrylamide), starch-carboxymethyl cellulose, hyaluronic acid-methylcellulose, chitosan, poly(N-isopropylacrylamide), and amino-terminated polyethylene glycol.
16. The lithium salt is LiNO 3 , LiOH, LiCl, LiBr, LiI, LiClO 4 , LiBF 4 , LiB 10 C 10 , LiPF 6 , LiCF 3 SO 3 , LiCF 3 CO 2 , LiAsF 6 , LiSbF 6 , LiAlCl 4 , C.H. 3 SO 3 Li, C.F. 3 SO 3 Li, LiSCN, LiC(CF 3 SO 2 ) 3 , (CF 3 SO 2 ) 2 NLi and (FSO 2 ) 2 The method for producing a composite solid electrolyte according to claim 1, wherein the composite solid electrolyte contains one or more selected from the group consisting of NLi.
17. 2. The method of claim 1, wherein a molar ratio of lithium ([Li]) to the molar concentration ([G]) of the second polymer is 0.1 to 0.
5.
18. The ionic conductivity of the composite solid electrolyte is 10 -5 The method for producing a composite solid electrolyte according to claim 1, wherein the surface area of the electrolyte is 0.2 S / cm or more.
19. 10. A composite solid electrolyte produced by the method of claim 1, comprising a ceramic ion conductor layer comprising a ceramic compound, a second polymer, and a lithium salt.
20. An all-solid-state battery comprising the composite solid electrolyte produced by the method of claim 1.
Citation Information
Patent Citations
Composite solid electrolyte based on inorganic ceramic three-dimensional aerogel skeleton support and preparation method thereof
CN113270634A
Porous ceramic body having macro-porous communicating pore and method of manufacturing the same
JP2008201636A
Composite Electrolytes
JP2022017247A
Composite electrolytes
US20220077495A1
Method for manufacturing LLZO solid electrolyte by polymer hydrid process and method for manufacturing secondary battery comprising the same
KR1020170045011A